Herpes Simplex Virus 2 Meningoencephalitis-Associated Bilateral Optic Neuritis and Radiculitis - Conte, William L. (Neuroophthalmology, 2019)
The most common ocular complication of herpes simplex virus (HSV) is acute retinal necrosis. We present a rare case of a patient with HSV-2 meningoencephalitis that developed severe vision-threatening optic neuritis. The patient was treated with steroids and IVIG, which allowed a rapid improvement in her vision.